A Medley with over ten years of (mostly) light-ion production measurements at the svedberg laboratory - S. Pomp (2018)
© Owned by the authors, published by EDP Sciences, 2010. Over the past years an experimental programme has been run at the neutron beam of The Svedberg Laboratory with the aim to study light-ion production induced by 96 and 175 MeV neutrons for a wide variety of targets. The measurements have been conducted using the Medley facility which allows measurement of p, d, t, He-3 and alpha production at fixed angles (from 20 to 160 degrees in steps of 20 degrees) over a wide dynamic range. An overview of the results obtained at the now finished campaign at 96 MeV will be given. Since 2007 we have been running at 175 MeV with C, O, Si, Fe, Bi and U as target material. Preliminary results from these measurements will be shown and compared to model calculations with Talys-1.2. We also summarize the Medley measurements of elastic np and nd scattering and of angular distributions of fission fragments.